2019
DOI: 10.1093/scan/nsz030
|View full text |Cite
|
Sign up to set email alerts
|

Happy you, happy me: expressive changes on a stranger’s voice recruit faster implicit processes than self-produced expressions

Abstract: In social interactions, people have to pay attention both to the ‘what’ and ‘who’. In particular, expressive changes heard on speech signals have to be integrated with speaker identity, differentiating e.g. self- and other-produced signals. While previous research has shown that self-related visual information processing is facilitated compared to non-self stimuli, evidence in the auditory modality remains mixed. Here, we compared electroencephalography (EEG) responses to expressive changes in sequence of self… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…More specifically, it was evidenced that self-generated movement sounds, such as one’s own finger snapping sounds, could elicit MMN, indicating that preferential processing of the characteristic sensory features of SRI (self-related movement sounds) occurred prereflectively and without being aware of it ( Justen and Herbert, 2016 ). Different from previous studies, Rachman et al (2019) investigated whether the same expressive changes (pitch variations, inflections, and timbre) were processed differently on self-voice compared to a stranger’s voice and found that strangers’ voice deviants generated earlier MMN onset responses, indicating that expressive changes on a stranger’s voice were highly prioritized in auditory processing compared to identical changes on self-voice. Although the above findings are inconsistent, it is generally believed that auditory SRI could elicit MMN, reflecting the preattentional change detection processing of SRI.…”
Section: Introductionmentioning
confidence: 65%
“…More specifically, it was evidenced that self-generated movement sounds, such as one’s own finger snapping sounds, could elicit MMN, indicating that preferential processing of the characteristic sensory features of SRI (self-related movement sounds) occurred prereflectively and without being aware of it ( Justen and Herbert, 2016 ). Different from previous studies, Rachman et al (2019) investigated whether the same expressive changes (pitch variations, inflections, and timbre) were processed differently on self-voice compared to a stranger’s voice and found that strangers’ voice deviants generated earlier MMN onset responses, indicating that expressive changes on a stranger’s voice were highly prioritized in auditory processing compared to identical changes on self-voice. Although the above findings are inconsistent, it is generally believed that auditory SRI could elicit MMN, reflecting the preattentional change detection processing of SRI.…”
Section: Introductionmentioning
confidence: 65%
“…( 2022c ; social action violations, N = 28), Heleven et al . (2019 ; social action sequence, N = 24) and Rachman et al . (2019 ; social voice sequence, N = 25), which have commonly employed sample sizes around 25.…”
Section: Methodsmentioning
confidence: 99%
“…MMN telah digunakan pada ranah penelitian kognisi sosial. Beberapa contoh: terhadap perubahan ekspresi suara orang lain dibandingkan suara diri sendiri (Rachman et al, 2019), respons terhadap suara emosional (C. Chen et al, 2018) pada bayi (Kostilainen et al, 2018), dan individu dengan spektrum autisme (Lindström et al, 2018), suara dari lawan jenis (Casado & Brunellière, 2016;Thornton et al, 2019). Sebuah penelitian cukup menarik dari Petrosino et al (2021) membandingkan tiga suara yang memiliki konotasi sosial: mengendus, batuk, dan kentut.…”
Section: Aplikasi Dan Potensi Penelitian Mmnunclassified